Advances of CD19-directed chimeric antigen receptor-modified T cells in refractory/relapsed acute lymphoblastic leukemia - Guoqing Wei; Lijuan Ding; Jiasheng Wang; Yongxian Hu; He Huang (Experimental Hematology & Oncology, 2017)
Abstract Refractory/relapsed B-cell acute lymphoblastic leukemia remains to be a significant cause of cancer-associated morbidity and mortality for children and adults. Developing novel and effective molecular-targeted approaches is thus a major priority. Chimeric antigen receptor-modified T cell (CAR-T) therapy, as one of the most promising targeted immunotherapies, has drawn extensive attention and resulted in multiple applications. According to published studies, CD19-directed CAR-T cells (CD19 CAR-T) can reach a complete remission rate of 94% in both children and adults with refractory/relapsed ALL, much higher than that of chemotherapy. However, the encouraging outcomes are often associated with complications such as cytokine release syndrome (CRS), serious neurotoxicity, and on-target off-tumor effect, which seriously impeded further clinical application of CAR-T cells. Moreover, CAR-T therapy is typically associated with high relapse rate. This article briefly reviews the manufacture technologies, the conditioning regimens, the cell infusion doses, as well as the prevention and treatment strategies of complications for CAR-T cell therapy.